(3fgL GdHdGZIs - (3CHh GdbGSe Ydj Hf GdMSjf Hf ehSi GdTQja GdeQJVj, GdTQja GdeQJVj,J (B436 (3g` s
(3ChdgG (B:s
(3CeG HYO MeOG ddg GdPi LYd GdMeO KefG dfYeGFg heYGPG ef HdGFg hSHjd Edi LfGJg s
(3BNQgG (B:s
(3hGdMeO ddg ChdG hBNQG hXGgQG hHGWfG hGdUdGI hGdSdGe Ydi eMeO QShd Gddg hYJQJg GdWGgQI hCSQJg GdaGNQI s
(3GdfSNI HgG MhGTs
(3PcQ CQHQi eagQS JTSJQHJi Cf JGQjN GdfSN (B1006 (3g`s
(3ai BNQ hQbI eG jKHJ CfgG ebGHdIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B295 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B81s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1991s
Keywords: (3GdCOHs